Protease‐sensitive regions in amyloid light chains: what a common pattern of fragmentation across organs suggests about aggregation. (15th September 2021) - Mazzini, Giulia; Ricagno, Stefano; Caminito, Serena; Rognoni, Paola; Milani, Paolo; Nuvolone, Mario; Basset, Marco; Foli, Andrea; Russo, Rosaria; Merlini, Giampaolo; Palladini, Giovanni; Lavatelli, Francesca
Abstract : Light‐chain (AL) amyloidosis is characterized by deposition of immunoglobulin light chains (LC) as fibrils in target organs. Alongside the full‐length protein, abundant LC fragments are always present in AL deposits. Herein, by combining gel‐based and mass spectrometry analyses, we identified and compared the fragmentation sites of amyloid LCs from multiple organs of an AL λ amyloidosis patient (AL‐55). The positions pinpointed here in kidney and subcutaneous fat, alongside those previously detected in heart of the same patient, were aligned and mapped on the LC's dimeric and fibrillar states. All tissues contain fragmented LCs along with the full‐length protein; the fragment pattern is coincident across organs, although microheterogeneity exists. Multiple cleavage positions were detected; some are shared, whereas some are organ‐specific, likely due to a complex of proteases. Cleavage sites are concentrated in 'proteolysis‐prone' regions, common to all tissues. Several proteolytic sites are not accessible on native dimers, while they are compatible with fibrils. Overall, data suggest that the heterogeneous ensemble of LC fragments originates in tissues and is consistent with digestion of preformed fibrils, or with the hypothesis that initial proteolytic cleavage of the constant domain triggers the amyloidogenic potential of LCs, followed by subsequent proteolytic degradation. This work provides a unique set of molecular data on proteolysis from ex vivo amyloid, which allows discussing hypotheses on role and timing of proteolytic events occurring along amyloid formation and accumulation in AL patients. Abstract : In immunoglobulin light‐chain amyloidosis (AL amyloidosis), fragments of the amyloidogenic light chain (LC) are always present in fibrillar deposits. We compared the fragmentation sites of amyloid LC from multiple organs of a patient. The fragments pattern coincides across tissues; multiple cleavage sites were concentrated in 'proteolysis‐prone' regions of the sequence, common to all tissues. This unique set of molecular data on ex vivo amyloid allows discussing hypotheses on role/timing of proteolysis in AL.